Evaluation of Speak Up!: a sexual violence prevention program for middle school youth - Cornelis, Hope M., author; Riggs, Nathaniel, advisor; Haddock, Shelley, committee member; Winokur, Marc, committee member (Colorado State University. Libraries, 2017)
Sexual violence (SV) is a pervasive crime that disproportionately affects young people. Despite the need for SV prevention initiatives with young adolescents, a majority of documented efforts to understand and prevent SV have targeted college-aged individuals. The purpose of this study was to evaluate Speak Up!, an intensive, school-based, gender-separated SV prevention program for middle school youth. The evaluation utilized pre and post-test data from 76 students, aged 11-15, who participated in Speak Up! during the 2014-2015 academic year. Participants completed self-report surveys, developed by the implementing organization, at baseline and immediately after the intervention. The survey measure assessed participants' adherence to unhealthy relationship/sexual norms, self-efficacy for bystander intervention, and rigidity in gender ideology. Main effects and moderating associations were examined using repeated measures analyses of covariance (RM ACOVAs) and Cohen's d effect size estimates comparing participants' pre and post-test mean scores. Results revealed significant improvements in participants' adherence to unhealthy relationship/sexual norms from pre to post-test, regardless of implementation modifications and gender. Additionally, findings indicated that girls showed greater pre-post changes on the outcomes than did boys (marginally significant). Although strong conclusions about program impact could not be derived due to study limitations, this study illuminates the promise of SV prevention with youth and the need for further exploration of how to effectively prevent SV with this population.